2016
DOI: 10.1111/apa.13310
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of functional somatic symptoms in children and referral patterns to child and adolescent mental health services

Abstract: Paediatric inpatients with more severe FSS were more likely to be referred to CAMHS, but referral reasons were generally vague and psychosocial information was frequently missing. Clinical guidelines are needed to improve and systematise mental health referrals for children with FSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
2
6
0
2
Order By: Relevance
“…Our study implicates that bio-genetic, psychological, and family factors are the key impact factors in adolescents with STs. As reported in a recent study, possible genetic and environmental factors contribute to somatic symptoms in children and adolescents 39 ; a result which appears to be consistent with our study. Previous studies also state an association between SD and depression or anxiety disorders 7 .…”
Section: The Environmental Impact Factors Of Adolescent Stssupporting
confidence: 94%
“…Our study implicates that bio-genetic, psychological, and family factors are the key impact factors in adolescents with STs. As reported in a recent study, possible genetic and environmental factors contribute to somatic symptoms in children and adolescents 39 ; a result which appears to be consistent with our study. Previous studies also state an association between SD and depression or anxiety disorders 7 .…”
Section: The Environmental Impact Factors Of Adolescent Stssupporting
confidence: 94%
“…This would help translate into paediatric practice the emerging knowledge on the relevance of psychiatric and psychosocial factors for the understanding and management of paediatric FSS. The hospital where this study was conducted is to be congratulated for supporting PL CAMHS and the study by Tøt-Strate et al (1), and in so doing leading the way for possible further developments in this field. M Elena Garralda (e.garralda@imperial.ac.uk) Centre for Mental Health, Imperial College London, London, UK…”
Section: Resultsmentioning
confidence: 98%
“…The hospital where this study was conducted is to be congratulated for supporting PL CAMHS and the study by Tøt‐Strate et al. , and in so doing leading the way for possible further developments in this field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several authors have point out that somatoform symptoms in adolescents population are one of the main reasons of access to primary care services for seeking professional help and performing a number of specialist examinations (Casini, 2015;Tøt-Strate et al, 2016). Indeed, it has been reported that approximately 25-50% of emergency department (ED) visits by adolescents are for non urgent and non organic problems (Alderman, 2012;Cozzi et al, 2017).…”
Section: Problem Statementmentioning
confidence: 99%